2012
DOI: 10.1140/epjc/s10052-011-1850-8
|View full text |Cite
|
Sign up to set email alerts
|

Transverse enhancement model and MiniBooNE charge current quasi-elastic neutrino scattering data

Abstract: Recently proposed Transverse Enhancement Model of nuclear effects in Charge Current Quasi-Elastic neutrino scattering

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…There are two features of this expression that affect the analysis of a 2p-2h event using Eq. (20), which is correct only for true QE scattering, i.e., a 1p-1h event. First, in the last section we have shown that, at forward angles, where the cross section is largest, the 2p-2h contributions are largest at small T µ , below the QE peak.…”
Section: Energy Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are two features of this expression that affect the analysis of a 2p-2h event using Eq. (20), which is correct only for true QE scattering, i.e., a 1p-1h event. First, in the last section we have shown that, at forward angles, where the cross section is largest, the 2p-2h contributions are largest at small T µ , below the QE peak.…”
Section: Energy Reconstructionmentioning
confidence: 99%
“…First, in the last section we have shown that, at forward angles, where the cross section is largest, the 2p-2h contributions are largest at small T µ , below the QE peak. When analyzing such events with the help of the one-body expression (20) this leads to a lower reconstructed neutrino energy than the true one. Second, while QE scattering is strongly forward peaked, the 2p-2h events are fairly flat (within a factor of 2) in lepton angle (see Figs.…”
Section: Energy Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern explanations of the recent experiments include the effects beyond the scope of the naive RFG and impulse approximation. Among these are various extensions of the standard (global) RFG model, such as local Fermi gas (LFG) model [37], local density approximation (LDA) [38], and spectral function (SF) approach [39][40][41][42][43][44][45][46][47][48]; relativistic mean field and relativistic Green's function models [49,50]; charged meson-exchange currents (MEC), intermediate Δ isobar or multi-nucleon excitations [51,52], short-range and long-range correlations (SRC and LRC) within random phase approximation (RPA) [53][54][55]; quantum-kinetic transport equations (implemented in the GiBUU code) [56,57]; parametrization of the observed enhancement in the transverse electron quasielastic response function (presumably because of MEC) [45,[58][59][60]; a variety of so-called superscaling models, e.g., SuSA [61,62], SuSAv2 [63,64], SuSAv2-MEC [65][66][67], and SuSAM * [68]. The most comprehensive microscopic and phenomenological models usually increase the CCQE cross sections at low energies, thus providing better data explanation without increasing M RFG A (see Refs.…”
Section: Introductionmentioning
confidence: 99%